Trustworthy Global Computing c - Ganty, Pierre; Loreti, Michele; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book constitutes the thoroughly refereed post-conference proceedings of the 10th International Symposium on Trustworthy Global Computing, TGC 2015, held in Madrid, Spain, in August/September 2015. The 10 revised full papers presented were carefully reviewed and selected from 19 submissions. The Symposium on Trustworthy Global Computing focuses on frameworks, tools, algorithms, and protocols for open-ended, large-scale systems and applications, and on rigorous reasoning about their behavior and properties.
Keywords: Computer science; Computer organization; Computer security; Mathematical logic; Computer Science; Systems and Data Security; Mathematical Logic and Formal Languages; Information Systems Applications (incl. Internet).; Computer Systems Organization and Communication Networks; Electronic books